Carbono tipo diamante em componentes de implantes dentários: avaliação das propriedades antimicrobianas e de adesão de Escherichia coli - Maquera Huacho, Patricia Milagros [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The study of DLC films is the subject of research due to their different properties including antibacterial properties. Rehabilitator in implant treatment, complications may occur, providing the infiltration of oral microorganisms for implant- abutmente interface. The aim of this study was to evaluate properties and wetting surface free energy from the values of the contact angle; antimicrobial properties bioadhesion and cytotoxicity of titanium discs coated with DLC. Escherichia coli was maintained on BHI at 37 ° C for 3 h and 24 h for antimicrobial test. For adhesion test, the discs were maintained in culture of E. coli for 90 minutes at 37 ° C and 20 minutes inside ultrasound. The ability to prevent the migration of bacteria into the implant - abutment interface was performed in dental implants External Hexagon connected with a torque of 32N and left in contact with E. coli for 24 h , and Polymerase Chain Reaction semi -quantitative was performed to confirm the sterility of the technique. Were quantified in CFU / ml in BHI agar for antimicrobial test, bacterial adhesion and infiltration. Cytotoxicity was performed using human keratinocytes ( HaCaT ) cultured in DMEM maintained in an atmosphere of 5% CO2 at 37 ° C and evaluated by the MTT colorimetric assay. The results of wettability, antimicrobial test, adhesion test and bacterial infiltration showed no statistically significant difference between the test groups. The surfaces of titanium and coated with DLC showed a slight decrease in cell viability with a statistically significant difference to the control group. The DLC is presented as biocompatible material with mild cytotoxicity without changing the surface properties, has no antimicrobial properties, does not interfere with bacterial adherence for E. coli and do not inhibit bacterial infiltration into the implant-abutment interface.

O estudo de filmes de Carbono tipo Diamante é objeto de pesquisas devido às suas diferentes propriedades incluindo propriedades antibacterianas. No tratamento reabilitador com implantes, podem ocorrer complicações, proporcionando a infiltração de microrganismos orais para a interface Implante-Componente protético. O objetivo deste estudo foi avaliar propriedades de molhabilidade e energia livre de superfície a partir dos valores do ângulo de contato; propriedades antimicrobiana, de bioadesão e citotoxicidade de discos de titânio recobertos com DLC. Escherichia coli foi mantida em meio BHI a 37ºC por 3 h e 24 h para teste antimicrobiano. Para adesão, os discos foram mantidos em cultura de E. coli por 90 minutos a 37ºC e 20 minutos em ultrassom. A capacidade de prevenção na migração de bactérias para o interior da interface Implante-Componente protético foi realizado em implantes Hexágono Externo, conectados com torque de 32N e deixados em contato com E. coli por 24h, e Reação em Cadeia da Polimerase semi-quantitativo foi realizado para confirmação da esterilidade da técnica. Foram quantificados em UFC/mL em BHI Ágar para o teste antimicrobiano, adesão e infiltração bacteriana. Para citotoxicidade foi utilizado queratinócitos humanos (HaCat) cultivados em meio DMEM mantidos em atmosfera com 5% de CO2 a 37°C e avaliados pelo teste colorimétrico MTT. Os resultados de molhabilidade, teste antimicrobiano, teste de adesão e Infiltração bacteriana não apresentaram diferença estatisticamente significante entre os grupos. As superfícies de titânio e recobertas com DLC apresentaram uma leve diminuição na viabilidade celular com diferença estatisticamente significante ao grupo controle. O DLC apresenta-se como material biocompatível com leve grau de citotoxicidade que não modifica as propriedades de superfície, não apresenta propriedades antimicrobianas... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Implantes dentários; Dental implants; Escherichia coli; Infiltração dentária